Peranan Profesionalisme Guru untuk Meningkatkan Kreativitas Siswa MAN Kota Banjar - Dida Hasanah (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2022)
In the whole educational process, learning and teaching activities are the most important activities. This means that the success or failure of achieving educational goals depends a lot on how the teaching and learning process is designed and carried out in a professional manner. The focus of this research is to determine the role of teacher professionalism through the creativity of MAN Banjar students. So the approach that is considered suitable in this study is a qualitative approach using a descriptive-analytic method. Regarding the problem of professional teacher competence, it includes four competencies, namely: pedagogic competence, personality competence, social competence, and professional competence, so as to provide motivation for students to work and be dedicated.